Analysis of The Influence of Tiktok's Social Media Marketing on Brand Equity, Brand Loyalty and Brand Experience on Halal Skincare Products - Inas Suroya Rahmadini; Rachma Rizqina Mardhotillah (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
This is because it relates to the suitability of the target market that has been made. The large number of different brand choices on the market encourages Wardah to be superior in competition, namely through good brand equity in order to seize market share and gain profits, because good brand equity will create added value for consumers to make repeated product purchases in the future. come. Given the very high competition, encouraging the cosmetic industry to carry out various strategies to win the competition. Wardah carries out various strategies to attract customers to make purchases, one of which is a strategy based on emotional motives, namely by reviewing the experience that users get from the product. This study aims to analyze the effect of social media marketing on brand equity, brand loyalty and brand experience. The research method uses quantitative methods with purposive sampling technique. The distribution of the questionnaire was made online via the Google form which was distributed to 240 respondents within one week. Analysis can in this study use Partial Least Square (PLS). The results of this study are that there is a significant influence between social media marketing on brand equity, brand loyalty and brand experience. Brand experience has an influence on brand loyalty and brand equity.